2019
DOI: 10.3847/1538-4357/ab1d4e
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Gamma-Ray Bursts Observed by Fermi-LAT: The Second GRB Catalog

Abstract: The Large Area Telescope (LAT) aboard the Fermi spacecraft routinely observes high-energy emission from gamma-ray bursts (GRBs). Here we present the second catalog of LAT-detected GRBs, covering the first 10 yr of operations, from 2008 to 2018 August 4. A total of 186 GRBs are found; of these, 91 show emission in the range 30-100 MeV (17 of which are seen only in this band) and 169 are detected above 100 MeV. Most of these sources were discovered by other instruments (Fermi/GBM, Swift/BAT, AGILE, INTEGRAL) or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
198
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(223 citation statements)
references
References 107 publications
25
198
0
Order By: Relevance
“…Here B and ρ 0 are the strength of the magnetic field and the rest-mass density, respectively. As in the BHNS case, the lifetime of the jet and its associated Poynting luminosity are consistent with typical sGRBs [20][21][22][23], as well as with the BZ mechanism. Note that in the GRMHD simulations reported in [31][32][33], where the magnetic field is confined to the NS interior, neither an outgoing outflow nor a jet were observed.…”
Section: Introductionsupporting
confidence: 80%
“…Here B and ρ 0 are the strength of the magnetic field and the rest-mass density, respectively. As in the BHNS case, the lifetime of the jet and its associated Poynting luminosity are consistent with typical sGRBs [20][21][22][23], as well as with the BZ mechanism. Note that in the GRMHD simulations reported in [31][32][33], where the magnetic field is confined to the NS interior, neither an outgoing outflow nor a jet were observed.…”
Section: Introductionsupporting
confidence: 80%
“…the collapsar jet case; Peng et al (2005)) and the identical micro-physical parameters (n, ǫ B , and ǫ e ) to the wide jet (Nakar, & Piran 2017) with the synchrotron slope of p ∼ 2 (based on the X-ray spectrum) and the narrow jet opening angle of 5.5 • , we confirmed that the expected narrow jet components in X-ray and radio bands can describe the observed light curves (Figure 2). Considering the prompt phase of GRB160623A missed by Fermi/LAT (Figure 1), the huge total energy (∼ 8.5 × 10 53 erg) is likely reasonable as same as other energitic (> 10 54 erg) Fermi/LAT events (e.g., Abdo et al 2009;Urata et al 2012;Ajello et al 2019). In fact, even the late phase radiation in 100MeV-10GeV reached (2.4 ± 0.3) × 10 52 erg (Ajello et al 2019).…”
Section: Jet Opening Angle and Cocoon Radiationmentioning
confidence: 75%
“…Considering the prompt phase of GRB160623A missed by Fermi/LAT (Figure 1), the huge total energy (∼ 8.5 × 10 53 erg) is likely reasonable as same as other energitic (> 10 54 erg) Fermi/LAT events (e.g., Abdo et al 2009;Urata et al 2012;Ajello et al 2019). In fact, even the late phase radiation in 100MeV-10GeV reached (2.4 ± 0.3) × 10 52 erg (Ajello et al 2019). This result therefore implies that the GRB160623A radio afterglow originated from a relativistic cocoon afterglow.…”
Section: Jet Opening Angle and Cocoon Radiationmentioning
confidence: 75%
See 1 more Smart Citation
“…2 For the LAT data, we also used the gtBurst code to make unbinned maximum likelihood analysis. According to Ajello et al (2019), we selected the Pass 8 P8R2 TRANSIENT020E V6 event class and the corresponding response function for the time window starting at the trigger time T 0 and ending at 100 s after the GBM trigger (bottom panel in Figure 1). Another time window starting at the trigger time T 0 and ending at 10000 s after the GBM trigger, we selected the Pass 8 P8R2 TRANSIENT010E V6 event class and the corresponding response function (Table 1).…”
Section: Introductionmentioning
confidence: 99%